Peningkatan Pemahaman Lansia Dalam Konsumsi Obat Dan Peran Jamu Sebagai Terapi Komplementer Di Dusun Kradenan - Kautsari, Farah Widya; Kiki Rizki Handayani (LPPM STIKES Madani, 2025)
As people age, the function of body organs gradually declines, increasing the risk of chronic diseases in the elderly. Some individuals undergo regular health check-ups and monitoring at healthcare facilities, while others choose herbal medicine (jamu) to address their health issues. This community service activity aims to encourage the community to wisely consume medications, both traditional and synthetic, to achieve therapeutic goals without causing undesired side effects. The activities were carried out using both direct and indirect methods. Direct methods included lectures using PowerPoint presentations, while indirect methods involved distributing leaflets. A total of 33 elderly and pre-elderly participants, accompanied by 8 elderly health post (posyandu) cadres, took part in this program. The results showed an improvement in participants' understanding of proper medication consumption and the correct use of herbal medicine.